677. Using a Multisectoral One Health Approach to Prioritize Zoonotic Diseases in the United States. (26th November 2018) - Krishnasamy, Vikram; Behravesh, Casey Barton; Varela, Kate; Goryoka, Grace; Oussayef, Nadia; Rooney, Jane; Dutcher, Tracey; Bond, Elaine; Hopkins, M Camille; Gibbs, Samantha
Abstract: Background: Emerging and endemic zoonoses continue to have adverse global impacts. One Health approaches promoting multisectoral, transdisciplinary collaboration are important methods to address zoonoses threats through disease surveillance, prevention, control, and response. We conducted a One Health Zoonotic Disease Prioritization (OHZDP) workshop in the United States (US) to identify zoonotic diseases of greatest national concern that should be jointly addressed by the Centers for Disease Control (CDC), US Department of Agriculture (USDA), Department of the Interior, and partners. Methods: We used CDC's OHZDP tool to prioritize zoonoses. Workshop participants selected criteria for prioritization, and developed questions and weights for each criterion. Questions were answered using available literature and expert opinion with subsequent scoring resulting in a ranked zoonotic disease list. After agreeing on a final prioritized disease list, participants used components of the One Health Systems Mapping and Analysis Resource Toolkit, developed by USDA and University of Minnesota, to review multidisciplinary coordination processes for the prioritized zoonotic diseases. Results: Participants selected epidemic or pandemic potential, disease severity, economic impact, introduction or increased transmission potential, and national security as criteria to prioritize 56 zoonoses. The eight prioritized zoonotic diseases for the US were zoonotic influenzas, salmonellosis, West Nile virus, plague, emerging coronaviruses (e.g., SARS, MERS), rabies, brucellosis, and Lyme disease. Agencies then discussed recommendations to enhance One Health approaches to surveillance, response, prevention, and control of the prioritized zoonoses. Key themes and next steps for further implementation of One Health approaches were identified. Conclusion: This OHZDP workshop represents the first use of a One Health approach to zoonotic disease prioritization in the United States. It is a critical step forward in US government agency collaboration using One Health approaches. Further, the workshop created a foundation for future US government One Health systems strengthening for the prioritized zoonoses. Disclosures: All authors: No reported disclosures.